Mobilização social, acontecimentos e opinião pública: o posicionamento estratégico do Comitê Popular dos Atingidos pela Copa em Belo Horizonte (Copac-BH) - Clara Soares Braga (2015)
This research focuses on the relationship between events, public opinion and social mobilization, from the case study of Affected People's Committee by the World Cup in Belo Horizonte (Copac-BH). Copac-BH is a collective that won expanded visibility during major popular protests that took place in Brazil in June 2013. Several conditions of its mobilization process were reconfigured due to these and other events and, because of this, it assumed different strategic positions along its history. The research problem is to identify the changes in the Copac-BH's strategic positioning in public opinion in the light of events that changed the conditions under which the process of mobilization was developing, analyzing how these changes were processed and to what extent impacted the actions of the Committee and the movement of the publics and public opinion around the cause. The methodology used in the analysis consisted of a mix of quantitative and qualitative procedures, having a corpora composed of internet publications (Facebook, various websites and blogs) and interviews with representatives of the Committee, three performed in this study and four available on YouTube. The time frame of the analysis is from January 2011, when the Committee was made public for the first time, until July 2014, closure of Fifa World Cup, event that caused its appearance.